Comparative research in adult education : global perspectives on participation, sustainability and digitalisation - Breitschwerdt, Lisa [Herausgeber]; Schwarz, Jörg [Herausgeber]; Schmidt-Lauff, Sabine [Herausgeber] (wbv Media GmbH & Co. KG, 2023)
"The volume presents research that emerges from the 9th international Adult Education Academy (2022), which brings together researchers, students and practitioners from around the world to share perspectives comparatively. More than 80 participants from almost 20 different countries have exchanged, compared and expanded their individual knowledge and experience on adult learning and education. This volume consisting of eight contributions (including one fundamental article beforehand) assumes that globalisation affects national, regional and local levels of adult learning and education. Transformational relations are observed and analysed through the lens of participation, sustainability and digitalisation. All contributions apply an international comparative research approach to empirically investigate these areas with their upcoming needs. This approach takes place under consideration of comparison as a research method which not only grounds on a long tradition and relies on a set of rules and techniques, but also on an inner attitude and sensitivity with which we look at the world and its global needs while trying to understand." (Publisher, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 2.1 Bildungstheorien; 370; Erwachsenenbildung; Vergleichende Bildungsforschung; Bildungstheorie; Bildungssystem; Globalisierung; Nachhaltige Entwicklung; Digitalisierung